Strategi Keberlanjutan Pembangunan Energi Terbarukan Jangka Panjang Indonesia: Kasus Biomassa Energi Terbarukan di Sektor Pertanian, Perkebunan dan Kehutanan Indonesia - Radhiana Radhiana; Syaifuddin Yana; Muzailin Affan; Zainuddin Zainuddin; Susanti Susanti; Kasmaniar Kasmaniar; Filia Hanum (Jurnal Serambi Engineering, 2023)
Until 2050, it is certain that Indonesia will continue to rely on fossil fuels. To lessen its dependence on diminishing fossil fuels, Indonesia is still searching for alternate energy sources. Considering the continuing fall in oil output, the development of alternative and renewable energy sources is crucial in order to eliminate reliance on imports. Indonesia has been encouraged to create long-term renewable energy to meet the community's energy needs by of enormous natural resource potential. This country with the moniker “megadiversity” must be cautious when assessing the possibilities of renewable energy sources derived from raw resources, particularly biomass energy. Agriculture, plantations, and forestry are the sectors that have the most potential to be utilized as biomass energy. The results of the debate indicate that agricultural waste has an annual energy potential of 614,7 million GJ. In addition, forest biomass has an annual energy potential of 141,500,000 GJ, and plantation crops also have the ability to be used as biomass energy.